Recortes e rasuras no corpo: sagrado e erotismo no Teorema de Pasolini - Vieira Júnior, Erly Milton (2006)
In 1968, Pier Paolo Pasolini, according his cinema of poetry article, makes Teorema, teling a story about a foreigner s visit (supposed divine) to a urban rich family, making possible a transgressive experience which questionates the reason s limits. This research proposes, at first, a new discussion about some concepts ( sacrality , erotism , body ), as presented in Pasolini s works, pitted to some Bataille, Eliade ande Augé s articles and books. We chose some elements of cinematographic language (the big shot, editing and free indirect subjetive take ) to analyse the corporal cuts (in time and space) in a Pasolinian cinema of poetry ,thinking the body as a transgressive space in wich sacred and erotic experiences happen.